ANALISIS KONTRIBUSI DAN EFEKTIVITAS PAJAK PENERANGAN JALAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SAROLANGUN - Evi Susanti (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2015)
This study aims to analyze the phenomenon behind the increase in Street Lighting Tax revenues, the growth of Street Lighting Tax revenues and contributions to local taxes and Local Own Revenue (PAD) has decreased. The results of the study concluded that the analysis of the target of Street Lighting Tax Contribution to Regional Original Income set by the Regional Wealth and Asset Management Revenue Service (DPPKAD) of Sarolangun Regency is not in accordance with the potential. This is because the contribution rate of street lighting tax to Local Own Revenue is low, with an average contribution of 0.36%. The results of measuring tax effort (Tax effort) show that the ability to pay taxes in Sarolangun Regency is already optimal, this increase in ability to pay taxes aims to increase tax revenues in the future, in this case especially Street Lighting Tax. The results of the calculation of the effectiveness of Street Lighting Tax show that tax collection in Sarolangun Regency has reached the target (effective), but the realization of Street Lighting Tax has not reached optimal.